نظام المساعدة القضائية على ضوء القانون رقم 09/02 - بوشارب, إيمان (University of Eloued جامعة الوادي, 2022)
إذا كانت الموارد المالية للمحامي تتمثل أساسا في أتعابه التي يأخذها مباشرة من موكليه والذي يبقى له وحده حرية تحديدها وتقديرها كما له كذلك حرية قبول الدفاع عن شخص ما لجأ إليه من عدمه، فإن المشرع الجزائري أكد في ظل قانون المحاماة الجديد عن استثناء من هذه الحرية يتمثل في وجوب امتثال المحامي مهما تكن درجته إلى قرار تعيينه في إطار المساعدة القضائية وفقا للمادة 11 منه، واحتراما لمهنة النبلاء فقد أعاد المشرع الجزائري ضبط القانون المتعلق بالمساعدة القضائية في 2009 بموجب القانون رقم 09/02 وكذا في 2011 بموجب نصه التطبيقي، أين حدد أتعاب المحامي المعين في إطار المساعدة القضائية بما يتناسب و الأوضاع الحالية، وعليه فإن هدف الدراسة هو التعريف بنظام المساعدة القضائية ووجوب استجابة الدفاع للقرار الذي يقضي بها وآثار الامتناع عن المثول لهذا القرار.If the financial resources of the lawyer are mainly represented in his fees that he receives directly from his clients, that he alone remains free to determine and evaluate as well as the freedom to accept the defense of the person who has or not recourse to The Algerian legislator has confirmed within the framework of the new legal profession that the exception to this freedom is that the lawyer, whatever his rank, must comply with the decision to appoint him within the framework legal aid in accordance with Article 11 thereof, And out of respect for the profession of the nobles, the Algerian legislator redefined the law on legal aid in 2009 by law n ° 02/09 and in 2011 according to its implementing text, where he determined the fees of the 'officially appointed lawyer within the framework of legal aid in proportion to current conditions. Thus, the objective of the study is to present the legal aid system, the need for the defense to respond to the decision, which stipulates it, and the effects of abstaining from appearing for this decision.
Legal aid system in regard of Law n ° 09/02
مقال
Keywords: لمساعدة القضائية. ; الدفاع ; الاتعاب ; المحامي; legal aid; defense; fees; lawyer; lawyer’s law.